COMPETENCIES OF TEACHERS AND COORDINATORS IN TWO EDUCATIONAL INSTITUTIONS OF BUCARAMANGA ABOUT UNIVERSAL DESIGN FOR LEARNING (Cuidado y Ocupación Humana, 2023)
Being able to identify the competences of teachers and coordinators of educational institutions on the universal design for learning (DUA) is necessary since this new teaching-learning approach oriented to the diversity of students, its purpose is to grant multiple forms of perception and expression, giving opportunities to minimize barriers for students. Under a research methodology from a quantitative and descriptive approach, through a structured survey the knowledge of teachers and coordinators will be determined, with a sample of 64 teachers and coordinators from 2 public educational institutions in Bucaramanga. Where it will be acquired as results that the population does not have the necessary knowledge about the DUA, however, the importance of its implementation is manifested, benefiting not only the students, but also the facilitation of the teaching process. As a conclusion, the need to train and guide teachers in the process of implementing it in their classrooms was seen, since they do not receive training or complementary guides that would help in the learning process of the students; It also became evident from the professional academic plan of the teacher that there is no proposal where the subject matter dealt with in this research is exposed, that according to Colombian laws and regulations, educational institutions must implement strategies to achieve the correct development of inclusive learning.
Keywords: SAD; Teachers; Coordinators; Competencies; Competencies; Inclusion; Learning